2023
DOI: 10.3390/jcm12237333
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Stress, Anxiety, Well-Being, and Sleep Quality in Pregnant Women throughout Gestation

Rosalia Pascal,
Irene Casas,
Mariona Genero
et al.

Abstract: Background: Maternal stress, anxiety, well-being, and sleep quality during pregnancy have been described as influencing factors during pregnancy. Aim: We aimed to describe maternal stress, anxiety, well-being, and sleep quality in pregnant women throughout gestation and their related factors. Methods: A prospective study including pregnant women attending BCNatal, in Barcelona, Spain (n = 630). Maternal stress and anxiety were assessed by the Perceived Stress Scale (PSS) and State-Trait Anxiety Inventory (STAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…Analogs to our study, the study with African Americans indicated that multiparous women experienced than nulliparous women longer sleep latency and more frequent sleep disturbances (e.g., nighttime and early morning awakenings) when it goes from the first trimester to the third trimester [ 24 ]. In the present study, the mean sleep latency score was 1.06 ± 0.89 respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Analogs to our study, the study with African Americans indicated that multiparous women experienced than nulliparous women longer sleep latency and more frequent sleep disturbances (e.g., nighttime and early morning awakenings) when it goes from the first trimester to the third trimester [ 24 ]. In the present study, the mean sleep latency score was 1.06 ± 0.89 respectively.…”
Section: Discussionsupporting
confidence: 53%
“…The period of pregnancy can be considered a psychological burden, when the woman is experiencing a strong psychological phenomenon associated with important functional changes. The pregnant woman can experience frequent mood changes, accusing fatigue, exhaustion, sleepiness, anxiety, depressive reactions and sometimes ending up being overwhelmed by states of agitation, euphoria [43].…”
Section: Psychological Changes Stress and Anxiety Factors During Preg...mentioning
confidence: 99%